A new method for evaluating the dissolution of orodispersible films. (May 2015) - Xia, Yiran; Chen, Fang; Zhang, Huiping; Luo, Chunlin
Abstract The aim of this research was to develop and assess a new dissolution apparatus for orodispersible films (ODFs). The new apparatus was based on a flow-through cell design which requires only a limited amount of dissolution medium and can automatically collect samples in short-time intervals. Compared with the dissolution method in Chinese Pharmacopeia, our method simulated the flow condition of the oral cavity and resulted in reproducible dissolution data and remarkably discriminating capability. Therefore, we concluded that the proposed dissolution method was particularly suitable for evaluating the dissolution of ODFs and should also be applicable to other fast-dissolving solid dosage forms.